KADASTER 4D: SEBUAH KENISCAYAAN MENURUT KONDISI GEOLOGIS INDONESIA - Tanjung Nugroho (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2013)
The geologic condition of the Indonesian archipelago; lying on the meeting zone of three big global tectonic plateswhich actively moves, often causes the rising of many faults in the region. The faults have various activities ranging from silentmotion to active motion category. Today there are many land parcels located on the faults. Some of them have been registeredat the local Land Office. Due to the active motion of the faults, it is possible that there are movements of the land position anddimension. This may cause disputes on land boundaries. The 4D Cadastre is aimed at anticipating the coming problems.Keywords: Tectonic activities, geologic faults, land parcels.